KEHIDUPAN PEDAGANG JAMU GENDONG (STUDI KASUS DI KOTA PEKANBARU) - Angrani, Anggie; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesia is well known as a country which a wealth of herbs and spices and also traditional plants. Because of the natural wealth, most of Indonesia society are able to process them become a useful thing for human health both for prevention and medical treatment. Herb is Indonesian traditional medicine has been used long ago and has been proven the benefits. Herb is a drinkwhich made of natural ingredients, part of plants such as salsify, leaves and bark. It also made of animal body such as bile goat or seahorse of crocodile. This study conducted to reveal about how life of herbal trader from taking the ingredients, making herb until selling herb. This study is used social action theory by Max Weber and economic moral theory merchant by Hans-Dieter Evers. This study used qualitative method. The result of this study showed that they had some differences in their activity as traders carrying medicinal. The differences were how to make herb, to sell herb, and their dress. However, it had similarity in taking the ingredients, the price andpayment cycle by customer. This activity based on considering the culture and economy. The result of this study is expected to be able to provide an overview to all those who needs information about life of traders carrying medicinal. Keywords : Social action, moral economy merchant, carrying medicinal